Electro-assisted ammonium persulfate activation to promote the introduction of N and S into TiO2 film: Enhancing its photoelectrocatalytic performance under solar. Issue 20 (28th October 2019) - Li, Changxin; Liu, Yan; Zhang, Yanzong; Long, Lulu; Shen, Fei; Yang, Gang; Zhang, Xiaohong; He, Yan; Wang, Lilin; Deng, Shihuai
Abstract: Abstract : Anatase phase NO x /S 6+ –TiO2 ( x = 0, 1) film with high solar-driven activity has been successfully prepared via electro-assisted oxidation processes. The morphological and structural properties of the film were characterized by scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray diffraction, while the optical property was detected by UV-vis-NIR absorption spectroscopy. The results showed that the NO x /S 6+ –TiO2 film was composed of "flower-like" microvoids structure and displayed broad and strong optical absorption at around 544 and 1500 nm. Transient photocurrent response, photoluminescence spectroscopy, and electrochemical impedance spectroscopy indicated that the generation and separation of photogenerated charges were significantly enhanced under simulated solar irradiation. The NO x /S 6+ –TiO2 film exhibited excellent photoelectrocatalytic activity for the degradation of methyl orange (MO), and the decoloration rate and TOC removal respectively reached 98.97 and 59.44% at 20 min under solar irradiation. The film still had good stability after reusing ten times. Furthermore, a possible mechanism of photoelectrocatalysis was suggested in MO degradation by using NO x /S 6+ –TiO2 film.